2010
DOI: 10.2341/10-047-l
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Resistance of Endodontically-treated Teeth: Effect of Combination Bleaching and an Antioxidant

Abstract: SUMMARYThis in vitro study assessed the fracture resistance of endodontically-treated teeth undergoing combination bleaching with 38% and 9.5% hydrogen peroxide gels as in-office and at-home bleaching techniques, respectively. In addition, the effect of an antioxidizing agent, sodium ascorbate, was investigated.Methods and Materials: Sixty maxillary premolars were endodontically-treated, received a glass ionomer barrier as a mechanical seal and were embedded in acrylic resin up to the cemento-enamel junction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 33 publications
3
42
1
2
Order By: Relevance
“…These results corroborate those of a previous study (18) that evaluated the flexural strength and modulus of elasticity of bovine teeth bleached with 10% CP during 6 h/day within a 14-day period. Conversely, Khoroushi et al (19) verified that the fracture resistance of endodontically treated teeth decreases after bleaching with different HP bleaching protocols. The structural alterations resulting from the action of the bleaching agents may be reversed by remineralization with fluoride substances (20) or using sodium ascorbate (19).…”
Section: Discussionmentioning
confidence: 99%
“…These results corroborate those of a previous study (18) that evaluated the flexural strength and modulus of elasticity of bovine teeth bleached with 10% CP during 6 h/day within a 14-day period. Conversely, Khoroushi et al (19) verified that the fracture resistance of endodontically treated teeth decreases after bleaching with different HP bleaching protocols. The structural alterations resulting from the action of the bleaching agents may be reversed by remineralization with fluoride substances (20) or using sodium ascorbate (19).…”
Section: Discussionmentioning
confidence: 99%
“…Others studies have reported that SA can also promote resistance to fracture of teeth after internal bleaching [44] reduce microleakage [45,46,47], and restored the decrease in the Ca/P ratio after bleaching [48]. Khoroushi et al [44] reported that the SA hydrogel gradually attains a yellowish color, and after seven days, it becomes dark yellow to orange [44]. If this gel remains for a long time in contact with the dental substrate, it can reverse the bleaching outcome [44].…”
Section: Effects Of Sodium Ascorbate In Other Dental Propertiesmentioning
confidence: 99%
“…When the antioxidant was applied before bleaching, less damage to the odontoblastlike cells MDPC-23 was found, suggesting the SA solution may protect against the deleterious effect of hydrogen peroxide [43]. Others studies have reported that SA can also promote resistance to fracture of teeth after internal bleaching [44] reduce microleakage [45,46,47], and restored the decrease in the Ca/P ratio after bleaching [48]. Khoroushi et al [44] reported that the SA hydrogel gradually attains a yellowish color, and after seven days, it becomes dark yellow to orange [44].…”
Section: Effects Of Sodium Ascorbate In Other Dental Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…28 -After-this-period,-the-pulpchamber-was-washed-with-5.0-mL-distilled-water,-dried-with-an-air-stream-and-restored-in-a-similarmanner-as-described-for-G1.-In-G4-(10SAs),-allprocedures-were-realized-similar-to-G3,-but-afterthe-crown-bleaching,-the-pulp-chamber-was-Nilledwith-10%-sodium-ascorbate-solution-(Aphoticário,-Araçatuba,-SP,-Brazil).--After-the-restoration,-the-teeth-were-againmaintained-at-37°C-and-after-24-hrs-submitted-tof r a c t u r e-s t r e n g t h-t e s t i n g-u s i n g-a n- …”
Section: % %mentioning
confidence: 99%